Bergin and Garfield's handbook of psychotherapy and behavior change - Lambert, Michael J. (John Wiley & Sons, 2013)
Praise for Bergin and Garfield's Handbook of Psychotherapy and Behavior Change, Sixth Edition'Not only is this a unique resource, it is the only book that all practitioners and researchers must read to ensure that they are in touch with the extraordinary advances that the field has made over the last years. Many of us have all five previous editions; the current volume is an essential addition to this growing, wonderful series.Peter Fonagy, PhD, FBA, Freud Memorial Professor of Psychoanalysis and Head of the Research Department of Clinical, Educational and Health Psychology, University College London'As either researcher or clinician living in the contemporary world of accountability, this invaluable edition of the Handbook is a must for one's professional library. Marvin R. Goldfried, PhD, Distinguished Professor of Psychology, Stony Brook University The classic reference on psychotherapy revised for the twenty-first century Keeping pace with the rapid changes that are taking place in the field, Bergin and Garfield's Handbook of Psychotherapy and Behavior Change, Sixth Edition endures as the most important overview of research findings in psychotherapy for professionals, academics, researchers, and students. This bestselling resource presents authoritative thinking on the pressing questions, issues, and controversies in psychotherapy research and practice today. Thorough and comprehensive, the new edition examines: New findings made possible by neuro-imaging and gene research Qualitative research designs and methods for understanding emotional problems Research in naturalistic settings that capitalizes on the curiosity of providers of services Practice-relevant findings, as well as methodological issues that will help direct future research.